Rabies virus and Histoplasma suramericanum coinfection in a bat from southeastern Brazil - Menozzi, Benedito Donizete [UNESP]; da Paz, Giselle Souza [UNESP]; Paiz, Laís Moraes; Garces, Hans Garcia [UNESP]; Adorno, Brunna Mayla Vasconcelos [UNESP]; Almeida-Silva, Fernando; Zancope Oliveira, Rosely Maria; Richini-Pereira, Virgínia Bodelão [UNESP]; Chechi, Jéssica Luana [UNESP]; Bagagli, Eduardo [UNESP]; Bosco, Sandra de Moraes Gimenes [UNESP]; Langoni, Helio [UNESP] (Wiley, 2020)
Bats are essential to the global ecosystem, but their ability to harbour a range of pathogens has been widely discussed, as well as their role in the emergence and re-emergence of infectious diseases. This paper describes the first report of coinfection by two zoonotic agents, rabies virus (RABV) and the fungus Histoplasma suramericanum in a bat. The bat was from the Molossus molossus species, and it was found during the daytime in the hallway of a public psychiatric hospital in a municipality in São Paulo State, southeastern Brazil. RABV infection was diagnosed by the direct fluorescent antibody test and mouse inoculation test. The fungus was isolated by in vitro culture. Both diagnoses were confirmed by molecular techniques. Phylogenetic analysis showed that the fungus isolate had proximity to H. suramericanum in the Lam B clade, while the RABV isolate was characterized in the Lasiurus cinereus lineage. Since the M. molossus bat was found in a peri-urban transition area (urban/peri-urban), the possibility of cross-species transmission of this RABV lineage becomes more plausible, considering that this scenario may provide shelter for both M. molossus and L. cinereus. These are relevant findings since there has been an increase in bat populations in urban and peri-urban areas, particularly due to environmental modifications and anthropogenic impacts on their habitat. Thus, the detection of two zoonotic agents in a bat found in a public hospital should raise awareness regarding the importance of systematic surveillance actions directed towards bats in urban areas.
Keywords: Bats; cross-species; histoplasmosis; Molossus; phylogeny; rabies virus